2020
DOI: 10.1038/s41598-020-63587-3
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of top-down focal attention and the cortical tracking of speech

Abstract: Many active neuroimaging paradigms rely on the assumption that the participant sustains attention to a task. However, in practice, there will be momentary distractions, potentially influencing the results. We investigated the effect of focal attention, objectively quantified using a measure of brain signal entropy, on cortical tracking of the speech envelope. the latter is a measure of neural processing of naturalistic speech. We let participants listen to 44 minutes of natural speech, while their electroencep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(78 citation statements)
references
References 71 publications
6
67
5
Order By: Relevance
“…Here, only for three participants one artifactual channel was identified. Spectral entropy was computed based on the analysis described in Lesenfants and Francart (2020) . For each one-min segment and channel, the spectrum from 8 to 32 Hz was computed using multitaper spectral analysis (7 tapers, MATLAB function: pmtm).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, only for three participants one artifactual channel was identified. Spectral entropy was computed based on the analysis described in Lesenfants and Francart (2020) . For each one-min segment and channel, the spectrum from 8 to 32 Hz was computed using multitaper spectral analysis (7 tapers, MATLAB function: pmtm).…”
Section: Methodsmentioning
confidence: 99%
“…A high spectral entropy indicates an equally distributed EEG spectrum. This means that the power in each frequency band is very similar, whereas a low spectral entropy indicates an EEG spectrum in which the power is concentrated in one frequency band ( Lesenfants and Francart, 2020 ). Lesenfants et al (2018) found increased spectral entropy when participants actively attended to a stimulus compared to when they did not attend to the presented stimulus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We presented the 5-minute blocks on purpose in the beginning and at the end to ensure the decoders we would create based on this data were optimized to decode the different 2-minute speech segments in between. We know, for example, attention and listening effort could shift during the measurement, which could influence neural speech tracking (Ding and Simon, 2012a;Lesenfants and Francart, 2020). To ensure understanding of the storyline, the participants read the story summary before the experiment started.…”
Section: Eeg Experimentsmentioning
confidence: 99%
“…One possible explanation is that differences in prediction tendency may result in differential allocation of attention depending on individual listening effort. For example, Lesenfants and Francart (2020) found that attention plays a crucial role in the cortical encoding of speech and showed an advanced encoding in frontal & fronto-central electrodes with focal attention. So far, differences in challenging listening situations with low signal-to-noise ratio (such as in a cocktail party situation) have often been linked to individual differences in selective attention (Kerlin et al, 2010).…”
Section: The Influence Of Prediction Tendency On Speech Tracking Decr...mentioning
confidence: 99%